(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
Abstract: The rapid development of digital communication has significantly influenced spoken and written language forms, particularly in online environments. Internet comments represent a unique linguistic space where features of spoken language are reflected in written form. This article investigates the allophonic features observed in internet comments in English and Uzbek. The study aims to identify how phonetic variations, sound substitutions, and informal pronunciation patterns are represented orthographically in online comments. Using a comparative approach, the research analyzes samples of internet comments from social media platforms in both languages. The findings reveal both language-specific and universal tendencies in allophonic representation, influenced by phonological systems, sociolinguistic factors, and digital communication norms.